Management Challenges at Film-Induced Tourism Heritage Attractions. Issue 4 (2nd October 2017) - Bąkiewicz, Justyna; Leask, Anna; Barron, Paul; Rakić, Tijana
ABSTRACT: In response to an increasingly competitive environment, a number of heritage visitor attractions (HVAs) have encouraged filming, as well as subsequent film-induced tourism, in order to raise their profile, generate revenue and differentiate themselves from other attractions. However, while film-induced tourism may bring benefits, it can also be problematic, especially at HVAs which have conservation at their core. This article identifies a variety of challenges that film-induced tourism has created at Rosslyn Chapel and Alnwick Castle, both UK-based HVAs popular among film-induced tourists. The findings show that film-induced tourism resulted in a number of challenges at both sites not solely related to an increase in visitor numbers but also changes in visitor profile and behavior. Film-induced tourism at both sites has not only influenced visitors' expectations but also preferences for heritage interpretation resulting in management tensions. This article concludes with a discussion of possible heritage management responses to these challenges.